2017
DOI: 10.1152/physrev.00037.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac T-Tubule Microanatomy and Function

Abstract: Unique to striated muscle cells, transverse tubules (t-tubules) are membrane organelles that consist of sarcolemma penetrating into the myocyte interior, forming a highly branched and interconnected network. Mature t-tubule networks are found in mammalian ventricular cardiomyocytes, with the transverse components of t-tubules occurring near sarcomeric z-discs. Cardiac t-tubules contain membrane microdomains enriched with ion channels and signaling molecules. The microdomains serve as key signaling hubs in regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 156 publications
(139 citation statements)
references
References 248 publications
(280 reference statements)
9
130
0
Order By: Relevance
“…There is currently no invasive or noninvasive tool that measures intrinsic cardiomyocyte health. cBIN1 is an integral protein in cardiomyocyte t-tubule biology [20,21] and beat-to-beat calcium transients [29][30][31]. Previously, our group found that BIN1 is transcriptionally decreased in HF and is also detectable in blood [22,23].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is currently no invasive or noninvasive tool that measures intrinsic cardiomyocyte health. cBIN1 is an integral protein in cardiomyocyte t-tubule biology [20,21] and beat-to-beat calcium transients [29][30][31]. Previously, our group found that BIN1 is transcriptionally decreased in HF and is also detectable in blood [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…A generic BIN1 ELISA measured plasma BIN1 levels correlated with cardiac health in patients with arrhythmogenic right ventricular cardiomyopathy [23]. More recently, we cloned the cardiac specific t-tubule isoform cBIN1 [20], which is enclosed in microparticles and released into blood [23,24,31]. In the present study, we introduce CS, which is derived from the inverse of plasma cBIN1 concentration measured by a specific ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…T-tubule remodeling and the resultant abnormal calcium transients are central to the pathophysiology of HF [13,17,[37][38][39][40][41][42][43][44][45]. Our groups and others have identified that t-tubule remodeling can be a consequence of reduced cBIN1 [9,10].…”
Section: Cbin1 Based Cs Is a Marker Of Biochemical Health Of Cardiomymentioning
confidence: 89%
“…cBIN1 is a ventricular cardiomyocyte t-tubule membrane scaffolding protein, which organizes membrane microdomains that regulate calcium transients and its levels are decreased in failing cardiomyocytes [13,18]. A known pathophysiological hallmark of HF is the development of LV hypertrophy [15,24,25].…”
Section: In Hfpef Patients Cs Correlates With LV Massmentioning
confidence: 99%
See 1 more Smart Citation